Optimalisasi Pelayanan Tuberkulosis melalui Asuhan Keperawatan Berbasis Keluarga: Pendekatan Studi Kasus - Syamsir, Syamikar Baridwan; Permatasari, Henny; Rachmawati, Utami; Herlinah, Lily; Setiawan, Agus; Supriyatno, Heru; Natashia, Dhea (PT. Pubsains Nur Cendekia, 2024)
Tuberculosis (TB) is a global health challenge that significantly impacts individuals and communities. Family-based care is recognized as an effective method to enhance TB management. The aim of this case study is to illustrate the implementation of family-based nursing care in a TB case to provide holistic care. The method used is a case study approach following the Family Nursing Model (FCN) theory by Friedman. A family with TB-diagnosed members was selected as the sample. The nursing care process was conducted over three months with bi-weekly routine visits. The care process included assessment, diagnosis, intervention, implementation, and evaluation stages. The results of this case study formulated the nursing diagnosis “Ineffective Health Maintenance in the Family of Mr. D”. Interventions were based on the five family health tasks, namely understanding health issues through education about TB and the disease process; making informed decisions involving the family; providing care with support for the treatment program undergone by family members; adapting a healthy environment through hygiene behavior education; and utilizing health services through referral to community services. This nursing care illustrates integrated care practices with active family involvement, providing practical guidance to enhance TB treatment outcomes and management at the family level.